Temperature-based crossmodal correspondences: causes and consequences - Spence, C (Brill Academic Publishers, 2020)
The last few years have seen an explosive growth of research interest in the crossmodal correspondences, the sometimes-surprising associations that people experience between stimuli, attributes, or perceptual dimensions, such as between auditory pitch and visual size, or elevation. To date, the majority of this research has tended to focus on audiovisual correspondences. However, a variety of crossmodal correspondences have also been demonstrated with tactile stimuli, involving everything from felt shape to texture, and from weight through to temperature. In this review, I take a closer look at temperature-based correspondences. The empirical research not only supports the existence of robust crossmodal correspondences between temperature and colour (as captured by everyday phrases such as ‘red hot’) but also between temperature and auditory pitch. Importantly, such correspondences have (on occasion) been shown to influence everything from our thermal comfort in coloured environments through to our response to the thermal and chemical warmth associated with stimulation of the chemical senses, as when eating, drinking, and sniffing olfactory stimuli. Temperature-based correspondences are considered in terms of the four main classes of correspondence that have been identified to date, namely statistical, structural, semantic, and affective. The hope is that gaining a better understanding of temperature-based crossmodal correspondences may one day also potentially help in the design of more intuitive sensory-substitution devices, and support the delivery of immersive AR and VR experiences.